PERAN INFLUENCER MEDIA SOSIAL SEBAGAI AKTOR DIPLOMASI BUDAYA KOREA SELATAN - Miftahul Khoiriyah Al Istiqomah; Anggy Wira Pambudi; Henike Primawanti (Hubungan Internasional, 2021)
This research eximines in how South korea's influencers taking a role as South Korea's culture diplomacy actor. This paper will analyze how South Korea's influencers create a creative content about their culture in order to get people's attention, so that it will be popular. This will give an impact not for the influencer but also for the south korea's culture itself. By using culture diplomacy and digital diplomacy theory this paper will analyze how South Korea's influencers create a creative content about their culture in order to get people's attention, so that it will be popular. This will give an impact not for the influencer but also for the south korea's culture itself. This study found that south korea's influencers have succeeded in popularizing south korea's culture that is created as a content that can be enjoyed by the global people.Keywords: South Korean, Social Media, Influencer, Content